Mali : Joint Staff Assessment of the Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report, 2004)
This paper presents the Joint Staff Assessment of the Poverty Reduction Strategy Paper (PRSP) Annual Progress Report for Mali. Mali's first annual PRSP Progress Report presents a frank assessment of implementation of the PRSP. The Progress Report highlights Mali's macroeconomic and policy outcomes, strategies, and sector-specific poverty reduction activities during 2002-03. It reviews the overall context in which the strategy was being implemented. It also provides recommendations based on an assessment of strengths and weaknesses noted during implementation of the strategy.